Effects of brewing conditions and organoleptic assessment of cascara from Coffea arabica L. - Endmarhuka, Alexandra; Syach, Adam Muchammad; Kumalaputri, Angelina Justina; Abduh, Muhammad Yusuf (Institut Teknologi Bandung, 2024)
The conversion of coffee cherries into coffee beans results in notable by-products, particularly coffee pulp. This by-product, such as cascara, has the potential for further valorisation to produce bioproducts with economic value, possessing high levels of antioxidants and ascorbic acid. This study aimed to determine the optimize variations in brewing conditions of Arabica (Coffea arabica L.) cascara on antioxidant activity and ascorbic acid. This study encompassed three brewing conditions, including temperature (80, 85, 90, and 95 °C), time (2, 4, 6, and 8 min), and volume (100, 150, 200, and 250 mL). The results revealed that the optimal brewing conditions in terms of antioxidant activity in Arabica cascara were brewing at a temperature of 90 °C for 2 min, using 100 mL of water while in terms of ascorbic acid content were brewing at a temperature of 80 °C for 8 min, using 250 mL of water. Subsequently, organoleptic assessments were conducted using brewing at a temperature of 90 °C for 2 min, using 200 mL of water with the mass ratio of cascara to herbal extracts (4:1, 4:2, and 4:3) including mint leaf, lychee, strawberry, and raspberry extracts. The preferred formulation for Arabica cascara tea involves brewing with a 4:1 mass ratio of cascara to mint leaf based on taste, aroma, and color. These findings provide valuable insights into the optimal brewing conditions for Arabica cascara on maximizing the antioxidant activity and ascorbic acid, and the inclusion of herbal extracts enhances its overall preference among panellists.